The U.S.A From Elt perspectives - Trần, Xuân Điệp (Đại học sư phạm, 2005)
This book is aimed at providing general information about the U.S.A and lead-into the following 17 units of the course. The 17 units are intended to give learners chances to learn about American culture by stuying the text and performing the following language tasks under the teacher's guidance. The 17 units represent 13 different topics, namely, getting along in America, America social relations, the country of the U.S.A, the American people, the history of the U.S.A., American Sports, the American attitude toward manual labor..Each unit is composed of: 1. word study;2. Reading suggestions; 3. Reading text; 4. Follow -up exercises